Managing pain in sport - Lancaster, M.; Robson, S.; Gifford, L.; Hamilton, A. (Peak Performance, 2008)
Pain: Questions and answers to help athletes understand how to manage and overcome pain (Matt Lancaster) Injury: Part one investigates a revolutionary approach to chronic injury, focusing on pain management - Part two presents specific case studies related to the previous chapter`s findings (Stephen Robson and Louis Gifford) Medicine: A guide to the dangers of pain relief medication (Andrew Hamilton)